A fatal footnote - Loudon, Margaret (Loudon, Margaret. Open book mysteries, 2021)
"Writer-in-residence Penelope Parish will need to use every trick in her quaint British bookshop to unravel a murderous plot that threatens to ruin a ducal wedding. The wedding of the Duke and Duchess of Upper Chumley-on Stoke has all the makings of a fairy tale, complete with a glowing bride and horse-drawn carriage. But it wouldn't be much of a story without a villain, and as American Gothic novelist Penelope Parish is coming to learn, happy-ever-afters are as fraught in this charming British town as they are in her books. When the Duke's former girlfriend is found murdered at the reception it's up to Penelope and her newfound family at the Open Book bookshop to catch the killer before they strike again"--FantasticFiction.com.